Interplay Between Membrane Permeability and Enzymatic Barrier Leads to Antibiotic-Dependent Resistance in Klebsiella Pneumoniae - Nicolas-Chanoine, Marie-Helene; Mayer, Noémie; Guyot, Kathleen; Dumont, Estelle; Pagès, Jean-Marie (Frontiers in Microbiology, 2018)
The interplay between membrane permeability alterations and the enzymatic barrier contributes to Klebsiella pneumoniae multidrug resistance. We assessed the specific effect of the efflux levels of the main efflux pumps (AcrAB and OqxAB), alone and associated with the loss of the main porins (OmpK35 and OMPK36), on the activity of various antibiotics by constructing a set of K. pneumoniae isogenic strains, including strains with plasmid-mediated β-lactamases (DHA-1, CTX-M-15 and OXA-48). The two pumps contributed to intrinsic chloramphenicol resistance and AcrAB to that of nalidixic acid and cefoxitin, whereas they had no impact on the activity of the other 11 antibiotics tested. We confirmed the expulsion of these three antibiotics by the two overproduced pumps and that of tigecycline by overproduced AcrAB, and showed that overproduced AcrAB also expelled ertapenem, piperacillin, ceftolozane, and ceftazidime. The sole loss of porins did not significantly affect the activity of the tested antibiotics, except ertapenem. The effect of efflux increases and porin loss on β-lactam activity was the highest in plasmid-mediated β-lactamase-producing strains. Thus, DHA-1-producing strains became non-susceptible (NS) to (i) ertapenem when there was an increase in efflux or porin loss, (ii) imipenem and ceftazidime+avibactam when the two mechanisms were associated, and (iii) temocillin when AcrAB was overproduced. The CTX-M-15-producing strains became NS to (i) ertapenem when there was no porin, (ii) ceftolozane+tazobactam when there was either overproduced OqxAB or porin loss, and (iii) temocillin when AcrAB was overproduced. OXA-48-producing strains known to be NS to temocillin were also NS to ceftolozane and they became NS to imipenem when the two pumps were overproduced or there was porin loss. Overall, this study shows that the balance between influx and efflux differentially modulates the activity of the tested antibiotics, an important point for evaluating the activity of future antibiotics or new combinations.